1987
DOI: 10.1073/pnas.84.23.8735
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of mRNA encoding nerve growth factor and its receptor in rat sciatic nerve during development, degeneration, and regeneration: role of macrophages.

Abstract: STRACTIn newborn rats the levels of nerve growth fa tor (NGF) mRNA (mRNANGF) and NGF receptor mRNA ( A') in the sciatic nerve were 10 and 120 times higher, r pectively, than in adult animals. mRNAL levels decreased st adily from birth, approaching adult levels by the third stnatal week, whereas mRNANUF levels decreased only after th first postnatal week, although also reaching adult levels by the third week. Transection of the adult sciatic nerve resulted in a marked biphasic increase in mRNANGF with time. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
305
1
4

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 604 publications
(332 citation statements)
references
References 26 publications
20
305
1
4
Order By: Relevance
“…31,32 Our examination showed a marked increase in NGF-IR in the PNS. Our model may have been easily influenced by conditions such as inflammation in the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 Our examination showed a marked increase in NGF-IR in the PNS. Our model may have been easily influenced by conditions such as inflammation in the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…31,52 On the other hand, in an immunohistological report examining the NGF receptors in traumatic human peripheral nerve neuroma, a marked increase in TrkA was observed. 53 Our study showed an increase in TrkA-IR in the PNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in 5-HT 3 R expression cannot be explained by changes in neurotrophin receptor expression by nodose neurons over this time in culture (D. W. and E. C., unpublished results). Because neurotrophins are released from non-neuronal cells in degenerating peripheral nerve stumps after axotomy (Heumann et al, 1987;Raivich et al, 1991), as well as from target tissues, this mechanism could ensure that, after a brief delay (24 hr), regenerating nodose axons will continue to express 5-HT 3 R. Conceivably, neurotrophins also play a role in regulating 5-HT 3 R expression in SCG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, our data indicates that the S100 + cells found in adult PNS following nerve injury are susceptible to death in the absence of axonal contact. A possible mechanism of S100 + Schwann cell death in adult mice is the up-regulation of the p75NGFR expression following axotomy (Heumann et al 1987). A role of p75NGFR in mediating cell death has been implicated in several cell types (Barrett and Bartlett 1994;Casaccia-Bonnefil et al 1996;Frade et al 1996;Rabizadeh et al 1993;Syroid et al 2000).…”
Section: Discussionmentioning
confidence: 99%